Corporate governance practices and financial performance of a manufacturing company a case study of coca cola beverages Uganda LTD - Jennifer Amek (Uganda Christian University, 2026)
The sought to establish how board composition affects financial performance, how effective the audit committee is, and how transparency and disclosure could impact financial performance. To achieve these goals, the research employed a mixed research design using the explanatory sequential method. The team gathered quantitative data through structured questionnaires answered by 27 respondents and backed up the results with secondary financial information. Financial performance, based on the perceptions of the respondents, was measured using a five-item instrument on a Likert scale. Descriptive statistics, correlations, and multiple regressions were employed using SPSS to analyze the data. The results indicate that there are strong and positive opinions regarding corporate governance practices, with the effectiveness of the audit committee being the highest (mean = 4.36). The second highest was transparency (mean = 4.28), followed by board composition (mean = 4.02). The correlations indicate that there are strong positive relationships between people’s perception of corporate performance and corporate governance practices, with the effectiveness of the audit committee being the highest (r = 0.81, p < 0.01). The second highest was transparency (r = 0.61, p < 0.01). Board composition was also significant (r = 0.44, p < 0.05). In the regression results, the three corporate governance practices explained 78.5% of the variation in perceived financial performance (R2 = 0.785, p < 0.001). The effectiveness of the audit committee was found to be the most important factor in perceived financial performance. The implications of this study are that good corporate governance has important implications for corporate performance outcomes and stakeholders’ perception of corporate financial performance outcomes, thereby making the organization more resilient and reducing agency costs. The recommendations are to emphasize audit committee expertise, reinvigorate whistle-blowing mechanisms, and improve board diversity. The study has implications for corporate governance in Uganda’s private manufacturing sector.
Undergraduate Research